1996
DOI: 10.1038/ki.1996.511
|View full text |Cite
|
Sign up to set email alerts
|

Specific receptor binding of renin on human mesangial cells in culture increases plasminogen activator inhibitor-1 antigen

Abstract: Some proteases possess a membrane receptor that focalizes their proteolytic activity on the cell surface and may mediate a proliferative effect, such as urokinase on glomerular epithelial cells. Since some hypertensive states are associated with high concentrations of renin and proliferation of arteriolar smooth muscle cells, we asked whether renin, an aspartyl-protease, would bind to mesangial cells that are smooth-muscle derived cells, which would induce their proliferation. The binding of 125I labeled recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
195
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(203 citation statements)
references
References 26 publications
4
195
1
3
Order By: Relevance
“…We conclude that prorenin does not act as an endogenous antagonist for the long-lasting effects of renin in the vascular wall. Evidence for renin binding to several receptors or proteins has been reported by several investigators, 7,8,10,25,26 who suggested that renin is actively taken up by tissues or into the cell. The extent of binding as well as the consequences of the binding differ markedly between organs.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that prorenin does not act as an endogenous antagonist for the long-lasting effects of renin in the vascular wall. Evidence for renin binding to several receptors or proteins has been reported by several investigators, 7,8,10,25,26 who suggested that renin is actively taken up by tissues or into the cell. The extent of binding as well as the consequences of the binding differ markedly between organs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Important among these new observations are studies demonstrating that (1) prorenin and renin can bind to specific cellular receptors with the generation of physiological effects, (2) prorenin, and to a lesser extent, renin, can be internalized by cells whereupon angiotensin II is produced, and (3) there exists a renin transcript in some cells that encodes a renin that is expected to be synthesized as an active, as opposed to a prorenin, and that is expected to remain in the cell because it lacks the sequence encoding the secretory signal piece (renin exon 1A). [2][3][4][5][6][7][8][9][10][11][12][13] These observations not only reveal prorenin and renin to be hormones in their own right, they suggest that prorenin and renin are intracrines.…”
mentioning
confidence: 86%
“…IGF-II receptors and/or give rise to the appearance of alternative (pro)renin receptors or uptake mechanisms (4,8,46,48,53).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the heart must sequester renin from the circulation to synthesize ANG II locally. Renin may diffuse into the interstitial space (18,28) or bind to renin receptors and/or renin-binding proteins (8,46,53). Because renin in blood is predominantly present in the form of its inactive precursor prorenin (11), it is also conceivable that the heart sequesters prorenin instead of renin.…”
mentioning
confidence: 99%